Complications and Gastropathies Associated with Nonsteroidal Anti-Inflammatory Drug use in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly utilized in pediatric medicine to alleviate pain and reduce fever. However, their use is not without risk, particularly concerning gastrointestinal (GI) complications. This article examines the incidence, mechanisms, clinical presentations, and management strategies of NSAID-induced gastropathies in children. Through a comprehensive review of current literature and case studies, the study highlights the pathophysiological effects of NSAIDs on the pediatric GI tract, emphasizing the need for vigilant monitoring and appropriate therapeutic interventions. The findings underscore the importance of balancing the therapeutic benefits of NSAIDs with their potential risks, advocating for informed clinical decision-making to mitigate adverse outcomes.Nonsteroidal anti-inflammatory medications, widely utilized for symptomatic relief in pediatric populations, exhibit therapeutic benefits including analgesia and antipyresis. Nevertheless, these agents can provoke gastrointestinal mucosal injury, ranging from superficial erosions to severe ulcerations and hemorrhage. This review critically examines the pathophysiological mechanisms underlying NSAID-induced gastropathies, incorporating recent pediatric clinical data, pharmacological profiles, and mechanistic insights. It highlights risk factors including dosage, treatment duration, co-administered drugs, and pre-existing gastrointestinal vulnerabilities. Emphasis is placed on diagnostic modalities such as endoscopic evaluation, laboratory biomarkers, and imaging techniques that facilitate early recognition of adverse outcomes. The review additionally explores preventive strategies, encompassing gastroprotective co-therapy, appropriate dosing regimens, and caregiver education, emphasizing clinical prudence in pediatric NSAID prescription. By integrating epidemiological evidence and mechanistic understanding, this study provides a comprehensive framework to optimize therapeutic efficacy while mitigating gastrointestinal risk in children.